THE DEVELOPMENT OF SCIENTIFIC BASED LKS ON ANIMAL AND PLANT TISSUES IN CLASS XI SCIENCE AT SMAN 10 GOWA: PENGEMBANGAN LKS BERBASIS SAINTIFIK PADA JARINGAN HEWAN DAN TUMBUHAN DI KELAS XI IPA SMAN 10 GOWA - Pratiwi, Nova Dwi; Arianto, Kornelis (Jurnal Biogenerasi, 2025)
This research aims to develop LKS based on a scientific approach to animal and plant tissue material for class XI Science at SMAN 10 Gowa, using the Dick & Carey development model so that the LKS is valid, practical and effective. The LKS development process follows seven modified stages, namely needs analysis, formulating specific objectives, developing instruments, developing strategies, developing LKS content, formative evaluation, and revision. The validation results from experts got a score of 3.5 which is included in the very good category, while the validation results from the class XI IPA2 biology teacher got a score of 3.35 in the very good category. Aspects assessed include introduction, appropriateness of content, appropriateness of presentation, appropriateness of language, and evaluation. Limited trials showed that students' responses to this worksheet obtained an average score of 73%, which was categorized as "effective". The results of learning observations showed a score of 3.5, which means this worksheet is classified as "practical". Based on these results, it can be concluded that the Biology LKS based on a scientific approach to animal and plant tissue material developed is suitable for use in learning trials for class XI Science with several revisions in accordance with the suggestions.